Depression, self-Injury, and suicidal ideation: an examination of the risk factors and psychosocial correlates among female college students - Bakken, Nicholas W. (Deviant behavior, 2024)
This research examines psychosocial risk factors of depression, non-suicidal self-injury (NSSI), and suicidal ideation among a sample of female college students. Data were collected from a random sample of 732 female college students attending a Midwestern public university. Logistic regression was used to investigate various risk factors of depression, NSSI, and suicidal ideation, including respondent demographic characteristics, mental health, sexual victimization, substance use, and sexual orientation. The results illustrate the co-occurring nature of these outcomes. Factors associated with significantly higher likelihood of depression, self-harm, and suicidal thoughts include low self-esteem, substance use, prior sexual victimization, and non-heterosexual orientation. The current study informs both our theoretical understanding of the etiology of these problem behaviors among college women and how to best develop and implement effective prevention and intervention programming.